2009
DOI: 10.3807/josk.2009.13.4.478
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Fabrication of the Cone Sheet for LCD Backlight Application

Abstract: An optical sheet with a cone array is designed, simulated, and fabricated in order to substitute the dual crossed prism sheets in the edge-type LCD backlight. The optimum structure of cone textures that is compatible with the dual crossed prism sheets was obtained by simulating the backlight installed with the cone array optical sheet. A SU-8 photoresist films of thickness 30~50 μm were spin-coated on a polyethylene terephtalate film (PET), and the cone texture array was formed by using the diffuse lithography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…For energy-coupling improvement between a light source and a light guide plate (LGP), a hybrid LED backlight [5] is fabricated by the LGP with the embedded LEDs inside to reduce the energy loss. For improvement of BEFs, a new cone sheet [6] is designed to replace conventional crossed BEFs. For development of compound optical film, a new light extraction film [7] and a lenslet brightness enhancement film (LBEF) backlight module [8] are designed for functions of both diffuser and conventional crossed BEFs.…”
Section: Introductionmentioning
confidence: 99%
“…For energy-coupling improvement between a light source and a light guide plate (LGP), a hybrid LED backlight [5] is fabricated by the LGP with the embedded LEDs inside to reduce the energy loss. For improvement of BEFs, a new cone sheet [6] is designed to replace conventional crossed BEFs. For development of compound optical film, a new light extraction film [7] and a lenslet brightness enhancement film (LBEF) backlight module [8] are designed for functions of both diffuser and conventional crossed BEFs.…”
Section: Introductionmentioning
confidence: 99%
“…For the energy-coupling improvement between the light source and the LGP, the hybrid LED backlight [3] is fabricated by the LGP with the embedded LEDs inside to reduce the energy loss. For the improvement of BEFs, a new cone sheet [4] is designed to replace the conventional crossed BEFs. For the development of compound optical film, the new light extraction film [5] and the lenslet brightness enhancement film (LBEF) backlight module [6] are designed for the functions of both diffuser and conventional crossed BEFs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the modeling and simulation of either the discharge characteristics for PDPs [8][9][10][11] or optical characteristics for liquid crystal displays adopting various optical films [12][13][14][15]. However, to the best of our knowledge, the modeling and simulation of the optical characteristics of PDPs, including the BRCR Simple Model of Bright-room Contrast Ratio Measurement System for … -Tae Won Beom et al performance, has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%